Electrophoretic Deposition and Characterization of Copper Selenide Thin Films - Abdul Razak, Mohd Fairul Sharin (2007)
Various methods have been developed to produce thin semiconductor films. One of the potential methods is electrophoretic deposition (EPD) due to simple experimental set up, shorter deposition time, low cost and versatility. EPD is a combination of two processes which is electrophoresis and deposition. Electrophoresis is a physico-chemical process, in which particle with surface charged move in a liquid medium under the effect of an applied potential. Deposition is the coagulation of particles into a dense mass on a substrate. In this study, copper selenide thin films were deposited on titanium substrate by electrophoretic deposition from copper selenide powder prepared by precipitation method. The deposition was carried out from copper selenide powder suspension in an organic mixture of methanol and toluene. Electrophoretic deposition was found suitable in the mixture solvent which allows the suspended particles to migrate to the electrode surfaces. The suspension was ultrasonicated for about 15 minutes before performing EPD. The crystalline structure, morphology, composition and thermal properties of the powder and the films deposited by EPD were characterized by using X-ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersive X-ray analysis (EDAX), and Thermogravimetric-Differential Thermogravimetric Analysis (TGA-DTG). The photoactivity of the films was analysed using linear sweep photovoltammetry (LSPV) in sodium thiosulfate solution. The band gap energy and transition type were determined from optical absorbance data. The powder consists of mixed phases of CuSe with a little CuSe2. The SEM micrograph of the powder showed inhomogeneous surface with sharp edges particles. TGA-DTG showed that CuSe phase in copper selenide solid is thermally stable below 350 º C. The films prepared at different voltages showed the formation of single phase CuSe. The films formation can be achieved in less than two minutes due to high deposition rate compare to other technique. All films prepared in this study showed p-type condition.. The deposition process is preferable to be performed at room temperature due to insignificant increased of photosensitivity at higher bath temperature. The sample showed indirect optical transition with band gap energy of 1.51 eV.